Current status and potentiality of class II bacteriocins from lactic acid bacteria: structure, mode of action and applications in the food industry. (February 2022) - Yi, Yanglei; Li, Ping; Zhao, Fan; Zhang, Tingting; Shan, Yuanyuan; Wang, Xin; Liu, Bianfang; Chen, Yujie; Zhao, Xin; Lü, Xin
Abstract: Background: Food preservation is important in increasing the shelf life of food and ensuring food safety. Investigations on food preservation have focused on meeting consumer demands for more natural and healthier food. Bacteriocins produced by lactic acid bacteria have caught the attention of food scientists to be used as natural food biopreservatives due to their antimicrobial activity against food spoilage and pathogenic bacteria. Class II bacteriocins are the largest bacteriocin family of lactic acid bacteria but have received disproportionately less attention than class I bacteriocins. Scope and approach: This article systematically compared the sequence property, 3-D structure, and mode of action of the four categories of class II bacteriocins of lactic acid bacteria. The current and potential applications of class II bacteriocins in the food industry have also been reviewed. A SWOT (Strength, Weaknesses, Opportunities and Threats) analysis of the different approaches and development on class II bacteriocins was performed. Key findings and conclusions: The class II bacteriocins produced by lactic acid bacteria have a variety of sequences and diverse properties, structures, and modes of action. Some of class II bacteriocins, e.g. pediocin, enterocin AS-48, plantaricin EF, are considered as attractive compounds in the food industry to prevent food spoilage and pathogenic bacterial growth. Elucidation of their characteristics and modes of action provides fundamental information in designing novel application strategies. The SWOT analysis will be helpful for current and future researches on class II bacteriocins. Highlights: The four sub-categories of class II bacteriocins of lactic acid bacteria have distinct properties. Class II bacteriocins exert antimicrobial activity through receptor recognition and/or electrostatic interaction. Class II bacteriocins are attractive antimicrobial compounds and have great potential in the food industry. A SWOT analysis on the development and application of classII bacteriocins has been performed.